The Application Of Resirculation System On Domestication Of Catfish (Pangasius polyuranodon Blkr) - Rio Yusufi Subhan; Iskandar Putra; Niken Ayu Pamukas; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Pangasius polyuranodon Blkr is Indonesia’s endemic spesies which need to bedomesticated for species preservation. The aim of this research is to find out thetechnique to domesticate P. polyuranodon Blkr from nature habitat and keep it incontrol aquaculture system, as well as also to apply resirculation system inkeeping it so that water quality is maintained well in order to support P.polyuranodon Blkr life. The method used in this research is experiment by usingComplete Random Design (CRD), where the treatments were P0 = unfilteredresirculation, P1 = sponge filter resirculation, P2 = active charcoal filterresirculation and P3 = zeolite filter resirculation. The result of this research is P.polyuranodon Blkr enable to domesticated in control aquaculture system. Thebest treatment from this research is P3 with amonia range from 0,08 – 0,11 mg/L,nitrat range is between 0,07 – 0,11 mg/L and nitrite range between 0,07 – 0,09mg/L. The P3’s treatment produce absolute growth of 9,24 g, the increase ofspecific growth 1,76%, the growth of biomass of 62,63 gr, the feeding efficiency28,06% and survival rate of 86,66%.Keywords: Pangasius polyuranodon Blkr, domestication, filterd resirculation,water quality, survival rate.